Conformational analysis, molecular structure, spectroscopic, NBO, reactivity descriptors, wavefunction and molecular docking investigations of 5, 6-dimethoxy-1-indanone: A potential anti Alzheimer's agent. Issue 1 (January 2022) - Sebastian, S.; Sylvestre, S.; Sundaraganesan, N.; Karthikeyan, B.; Silvan, S.
Abstract: The objective of the present study is focused to elucidate the structure of potential anti-Alzheimer's compound 5, 6-Dimethoxy-1-indanone (5, 6-DMI) and study its binding interaction towards the active site by molecular docking studies. The structural and various spectroscopic tools are used to understand the various interaction behaviors of the title compound. The theoretical calculation of 5, 6-DMI molecule is computed by Gaussian 09W software with Density functional B3LYP and CAM-B3LYP method utilizing 6-311G(d, p) as basis set. The Natural Bond Orbital (NBO) analysis has been performed to find all possible transition was correlate with electronic transition. The Non covalent interaction of 5, 6-DMI molecule was examined by adopt Reduced Density Gradient (RDG) analysis and colour filled ELF diagram. Molecular docking results suggest that 5, 6-DMI may exhibit inhibitory activity against apoE protein and may act as potential against Alzheimer's disease. Abstract : 5, 6-dimethoxy-1-indanone; Vibrational spectra; Wavefuntion; Molecular docking; Alzheimer's disease.